Metabolic control and cardiovascular risks among type 2 diabetes in a primary care clinic - Cheong, Ai Theng; Ahmad, Zaiton; Chew, Boon How (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2012)
Background: Prevalence of diabetes is escalating both globally as well as in Malaysia. With the epidemic of diabetes and its related morbidities and mortalities, health care professionals are facing an unprecedented challenges in controlling the disease. Objective: To determine the metabolic control and the cardiovascular risk factors among type 2 diabetic patients in a primary care setting. Method: This was a cross sectional study conducted in a primary care clinic in Selangor, Malaysia. Inclusion criteria were all type 2 diabetic patients aged 18 and above and were being followed-up for more than six months prior to the recruiting period in May 2009. The demographic data were obtained through faceto- face interview. Height, weight and blood pressure of the patients were taken during the day of data collection. The co-morbidities and laboratory results were obtained from the medical records. Results: Two-hundred patients were recruited. The mean age was 58.6 (SD=10.5) with 79.0% of the patients aged more than 50 years old. The majority of the patients were female (62.5%). One-tenth (11.5%) were smokers. More than half of the patients (64.0%) had co-morbid of hypertension and half of them (50.5%) had dyslipidaemia. A total of 72.5% of the patients had 3 or more cardiovascular risk factors. Less than one fifth of the patients had achieved the target of control for glycaemia, blood pressure, LDL and BMI. Those age 60 and above had significantly higher proportion of patients achieving fasting blood glucose control (p=0.033). Conclusion: The majority of type 2 diabetic patients had multiple cardiovascular risk factors (3 or more risk factors) and had not achieved the recommended goals in metabolic control.